Anti-fungal Activity of Punica Granatum I.peels Powder and Extracts from Pathogenic Samples - Siham S.Shaokat; Hamoudi A.Hameed; Hassan J.Mohammad (College of Pharmacy University of Baghdad, 2017)
Thirty five samples were collected from patients (1-30) years old, suffered from, infected skin , rushes, boils , oral thrush, anal & vaginal itches.  Candida albicans 57.3% (20 isolates) and Candida tropicalis 22.5% (8 isolates) Aspergillus  fumegatus 11.5% (4 isolates)   Aspergillus nigar 8.7%(3 isolates) , were isolated & identified from these samples.  Alcoholic & water hot extracts of the punica granatum (Pomegranate) peels as well as the dried powder were prepared.  The anti-fungal activity of the extracts was evaluated by means of the agar-well diffusion assay. The extract exhibited potent activity against yeast. The Minimum inhibitory concentrations were 128-1024 Î¼g/ml against Candida albicans and Candida tropicalis .Their was little difference between the activities of alcoholic extract & aqueous extract. These results suggest the Pomegranate Peels extract which contains gallotanic acid as a promising anti-fungal agent. Key wards : Antifungal agents, Plant extracts, Candida isolation